(untitled) (Bangladesh Journal of Infectious Diseases, 2018)
Background: The genus Enterococcus is of increasing significance as a cause of nosocomial infections and this trend is exacerbated by the development of antibiotic resistance. Objective: The aims of this study was to find out the susceptibility pattern and the prevalence of virulence genes in Enterococcus strains isolated from urinary tract infection in Bangladesh. Methodology: This cross-sectional study was conducted in the Department of Microbiology at Dhaka Medical College, Dhaka from January 2015 to December 2015 for a period of one (01) years. All the admitted patients in the Dhaka Medical College & Hospital, Dhaka and Banghabandhu Sheikh Mujib Medical University, Dhaka who were presented with clinical features of urinary tract infection at any age with both sexes were included as study population. The antimicrobial susceptibility of the strains was determined using the disk diffusion method; vancomycin susceptibility pattern was detected by MIC method. PCR was performed for the detection of genus-species, vanA, vanB gene and potential virulence genes. Result: Out of 84 Enterococci, majority (71.42%) of the isolates were E. faecalis followed by 23.81% were E. faecium. Regarding antimicrobial susceptibility pattern, 100% isolated Enterococci were sensitive to vancomycin, linezolid and teicoplanin. Most of the Enterococci were resistant to ciprofloxacin and ceftriaxone (92.86%) followed by 88.10% to gentamicin and 85.71% to azithromycin and rifampicin. No VRE was identified and the range of MIC for vancomycin was 1-4 µg/ml. None of the Enterococci was positive for vanA and vanB genes. Out of total E. faecalis and E. faecium, 87.50% were positive for ebp and 77.5%, 72.5%, 55.0%, 45.0%, 40.0% and 10.0% of isolates were positive for gelE, esp, ace, cyl, asa and hyl respectively. Conclusion: Almost all the virulence genes were more prevalent in E. faecalis isolates. Bangladesh Journal of Infectious Diseases 2017;4(2):30-34